Ionic conduction mechanism study in PMMA/DPNR electrolyte / Hilmi Raimi Noor Bakri - Noor Bakri, Hilmi Raimi (2007)
Thin, transparent and flexible free standing film can be obtained from PMMA/DPNR blend film when prepared by solvent casting method. From the FTIR analysis, it was confirmed the formation of polymer-salt complex that occur at the carbonyl group of PMMA. The lithium ion transparent in the system obeys the Arrhenius behavior at which the migration of cation is via ion hopping that is thermally assisted